CD8+ T cell exhaustion and cancer immunotherapy. (10th April 2023) - Wang, Qingda; Qin, Yang; Li, Bo
Abstract: Immunotherapy plays an increasingly important role in the treatment of most malignant tumors, and CD8 + T cells are the most important antitumor effector cells in the process of immunotherapy, and their number and functional status largely determine the antitumor effect. However, under continuous antigen exposure and the stimulation of inflammatory factors, CD8 + T cells gradually show a weakened proliferation and effector function, accompanied by the expression of a variety of inhibitory receptors. This state is known as CD8 + T cell "exhaustion" and often leads to the loss of control and progression of tumors. Recent studies provided us a better understanding of the mechanisms of T cell exhaustion, this review provides an overview of the activation, exhaustion mechanisms and exhaustion characteristics of CD8 + T cells. Although immunotherapy can reverse the exhaustion of CD8 + T cells and significantly improve the antitumor effects, single immunotherapy often has limitations, and it is difficult to achieve satisfactory antitumor effects, therefore, this review also summarizes up-to-date information related to cancer immunotherapy, and these emerging insights provide promising clues to the future management of malignant tumors. Highlights: CD8 + T cell exhaustion is one of the main factors that limit the efficacy of cancer immunotherapy. T cell exhaustion represents a distinct state of T cell differentiation, and exhausted CD8 + T cells possess an obviously different transcriptome from memory and effector CD8 + T cells. Single immunotherapy has limitations and is difficult to achieve satisfactory antitumor effects, combination immunotherapy has greatly improved the antitumor efficacy. Novel immunotherapeutic agents, more effective combination immunotherapy, and accurate biomarkers may be the future directions of immunotherapy research.